The Role of Local Communities in Ecotourism Development: A Bibliometric Analysis of Participation and Empowerment - Judijanto, Loso; Harsono, Iwan; Ramdhani, Rahmat (West Science Interdisciplinary Studies, 2024)
This study utilizes VOSviewer, a tool for constructing and visualizing bibliometric networks, to analyze the landscape of research within ecotourism and community development. Through a series of visualizations, we identified thematic clusters that encapsulate key focus areas such as community development, conservation efforts, economic impacts, and the integration of local culture and wisdom into sustainable tourism strategies. Our analysis further reveals how research trends have evolved from foundational to more specialized topics, particularly noting a marked focus on marine ecotourism and capacity building in recent years. Additionally, author collaboration patterns were examined to identify both prominent partnerships and potential gaps in collaborative research. The visualizations also highlighted underexplored areas that present new research opportunities, particularly in assessing the economic implications of ecotourism and developing capacity-building strategies. This comprehensive examination not only maps the current state of the field but also points towards future directions for research and collaboration.